Evaluation of Arabic Teaching Methods in Preparation for the TOAFL Exam - Ruhul Kudus; Siti Mutmainnah (Department of Arabic Education of State Collage for Islamic Studies of Mandailing Natal, 2024)
This study aims to evaluate various Arabic language teaching methods used in preparation for the Test of Arabic as a Foreign Language (TOAFL) exam. The various teaching methods evaluated in this study include communicative methods, audiolingual methods, use of technology, and task-based approaches. Each of these methods was analysed to see how well they assisted students in developing the skills necessary for success in the TOAFL exam. This research uses a literature study approach and critical analysis to assess the advantages and disadvantages of each method. The data used in this study were collected from various academic sources relevant to foreign language teaching, particularly Arabic. Using critical analysis, the researcher evaluated the effectiveness of each method in the context of learning Arabic for non-native speakers. The results of the analysis show that communicative methods provide effective results in improving speaking and listening skills. However, the success of this method is highly influenced by the active involvement of students and the ability of the teacher to create an interactive learning atmosphere. Meanwhile, the audiolingual method places a strong emphasis on mastering grammar and vocabulary, but has weaknesses in the context of its application to real communication. The use of technology in teaching allows for greater flexibility and accessibility, supports independent learning and provides access to a variety of learning materials. However, there are challenges related to limited access to technology and the need for personalisation of learning. Task-based approaches can increase motivation and language application skills in real-life situations, but require careful design and additional support from teachers. This research concludes that the integration of different teaching methods can create a more comprehensive learning experience. By utilising the advantages of each method, students can be optimally prepared for the TOAFL exam and develop Arabic language skills holistically.